Functional activity of blood eosinophils in patients with Opisthorchis felineus invasion - V. V. Tsukanov; N. E. Veselova; A. A. Savchenko; O. A. Kolenchukova; I. I. Gvozdev; A. V. Vasyutin; J. L. Tonkikh; E. V. Kasparov; A. G. Borisov; E. G. Gorchilova; M. Yu. Olkhovskaia; N. O. Prokopieva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. To study the functional activity of blood eosinophils in patients with Opisthorchis felineus (O. felineus) invasion.Material and methods. A total of 328 patients with O. felineus invasion (120 men and 208 women, mean age 40.3 years) and 34 practically healthy patients (14 men and 20 women, mean age 41.1 years) aged 18 to 70 years were examined. The main method for diagnosing opisthorchiasis was the determination of eggs or bodies of adult parasites in the duodenal contents and/or feces, which was used in all 328 patients with opisthorchiasis. All patients underwent a complete blood count and biochemical blood test, esophagogastroduodenoscopy and ultrasound examination of the abdominal organs. The study of the functional activity of blood eosinophils was carried out in 42 patients with opisthorchiasis and 34 healthy individuals from the control group by chemiluminescent analysis with the measurement of the intensity of production of reactive oxygen species in spontaneous and zymosan-induced reactions in lucigenin- and luminol-dependent processes.Results. The frequency of eosinophils in the complete blood count above 5% in the examined patients with opisthorchiasis was 19.5%. An increase in the content of eosinophils in the blood in patients with opisthorchiasis was associated with an increase in the frequency of complaints of pain in the right hypochondrium, pruritus, skin rashes, an increase in the proportion of leukopenia and neutropenia, an increase in the level of gamma-glutamyl transpeptidase in the blood, and an increase in the frequency of ultrasound signs of cholecystitis. At the same time, a pronounced increase in the functional activity of blood eosinophils, determined by the chemiluminescent method, was observed in patients with O. felineus invasion.Conclusions. Patients with O. felineus invasion with an increase in the content of eosinophils in the blood due to the likelihood of an aggressive course of the pathology deserve the close attention of practitioners with the need for a thorough comprehensive examination of patients, including immunological methods.